Lehninger principles of biochemistry - Nelson, David L.; Cox, Michael M.; Lehninger, Albert L.
"Lehninger Principles of Biochemistry ... brings clarity and coherence to an often unwieldy discipline, offering a thoroughly updated survey of biochemistry's enduring principles, definitive discoveries, and groundbreaking new advances with each edition.This new Seventh Edition maintains the qualities that have distinguished the text since Albert Lehninger's original edition--clear writing, careful explanations of difficult concepts, helpful problem-solving support, and insightful communication of contemporary biochemistry's core ideas, new techniques, and pivotal discoveries. Again, David Nelson and Michael Cox introduce students to an extraordinary amount of exciting new findings without an overwhelming amount of extra discussion or detail."--
The foundations of biochemistry -- I. Structure and catalysis. Water -- Amino acids, peptides, and proteins -- The three-dimensional structure of proteins -- Protein function -- Enzymes -- Carbohydrates and glycobiology -- Nucleotides and nucleic acids -- DNA-based information technologies -- Lipids -- Biological membranes and transport -- Biosignaling -- II. Bioenergetics and metabolism. Bioenergetics and biochemical reaction types -- Glycolysis, gluconeogenesis, and the pentose phosphate pathway -- Principles of metabolic regulation -- The citric acid cycle -- Fatty acid catabolism -- Amino acid oxidation and the production of urea -- Oxidative phosphorylation -- Photosynthesis and carbohydrate synthesis in plants -- Lipid biosynthesis -- Biosynthesis of amino acids, nucleotides, and related molecules -- Hormonal regulation and integration of mammalian metabolism -- III. Information pathways. Genes and chromosomes -- DNA metabolism -- RNA metabolism -- Protein metabolism -- Regulation of gene expression -- Abbreviated solutions to problems -- Glossary -- Index.
Previous edition 2013.
Includes bibliographical references and index.
Keywords: Biochemistry; Biochemistry -- Problems, exercises, etc; Biochemical Phenomena; Biochemical Phenomena; Energy Metabolism; Biochemistry